Quantification of interaction frequency between antigen-presenting cells and T cells by conjugation assay - Cerny, Ondrej (Methods in cell biology, 2023)
Interaction between an antigen-presenting cell and a T cell, and their subsequent conjugation are a prerequisite for the formation of the immunological synapse and productive, antigen-dependent activation of T cells. This initial interaction is accompanied by recognition of the presented antigen by the T cell receptor, and by changes in the morphology of the interacting cells and in actin cytoskeleton structure in the site of interaction. The experimental protocol below describes a simple assay for quantitative assessment of antigen-presenting cells-T cell conjugation using confocal microscopy or flow cytometry.
Keywords: T-lymfocyty; aktivace lymfocytů; Immunological synapse; receptory antigenů T-buněk; imunologické synapse; Antigen-Presenting Cells; Lymphocyte Activation; Conjugation assay; Receptors, Antigen, T-Cell; T-Lymphocytes; mikrofilamenta; Confocal microscopy; antigen prezentující buňky; B3Z; Flow cytometry; MutuDC; Immunological Synapses; Actin Cytoskeleton